2016
DOI: 10.1186/s12891-016-1245-y
|View full text |Cite
|
Sign up to set email alerts
|

Swedish Sonographers’ perceptions of ergonomic problems at work and their suggestions for improvement

Abstract: BackgroundSonographers’ perceptions of ergonomic and work-related pain problems at work have so far mostly been researched in quantitative studies by questionnaires. There is a need of experience-based research to deepen the knowledge about how sonographers perceive ergonomic problems at work. Therefore, the aim of this qualitative study was to describe sonographers’ perceptions of ergonomic problems at work, and their suggestions for improvement strategies.MethodsTwenty-two female sonographers were individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…In a study from 2016, the authors concluded that ultrasonographers consider their work stimulating but also physically exhausting. They are aware of the ergonomic positions during work, though the comfort of the patient and obtaining good ultrasonographic images often took precedence over the work position (31).…”
Section: Discussionmentioning
confidence: 99%
“…In a study from 2016, the authors concluded that ultrasonographers consider their work stimulating but also physically exhausting. They are aware of the ergonomic positions during work, though the comfort of the patient and obtaining good ultrasonographic images often took precedence over the work position (31).…”
Section: Discussionmentioning
confidence: 99%
“…The sonographers showed a high prevalence of pain in neck and upper limb and were exposed to several well-known ergonomic and organisational risk factors. Optimizing working condition may reduce pain and based on the associations at baseline as well as on knowledge from the literature [4,5,[25][26][27][28][29][30] we would like to make some recommendations. We recommend the equipment to be possible to adjust to fit the examiner's anthropometrics and to allow variation in work technique.…”
Section: Recommendationsmentioning
confidence: 99%
“…Sonographers have also reported that perceived poor lighting, e.g. glare or dazzle in the screen, leads to eyestrain and musculoskeletal discomfort [5]. There is limited evidence for the effects of visual interventions to prevent visual symptoms among computer users [34].…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 This was reflected in the work by Monnington et al, 9 who reported that sonographers use increased transducer force when scanning obese patients. Gemark Simonsen and Gard 10 reported that cardiac sonographers’ extended examination times and increased transducer pressure when scanning obese patients contributed to increased transducer grip force. The authors of the study 10 found that inexperienced sonographers who take longer to scan also suffer due to increased force applied to the transducer.…”
Section: Introductionmentioning
confidence: 99%